Tolvaptan use during hyperhydration in paediatric intracranial lymphoma with SIADH. (1st November 2016) - Willemsen, Ruben H; Delgado-Carballar, Violeta; Elleri, Daniela; Thankamony, Ajay; Burke, G A Amos; Nicholson, James C; Dunger, David B
Summary: An 11-year-old boy developed severe syndrome of inappropriate antidiuretic hormone secretion (SIADH) after diagnosis of an intracranial B-cell lymphoma. His sodium levels dropped to 118–120 mmol/L despite 70% fluid restriction. For chemotherapy, he required hyperhydration, which posed a challenge because of severe hyponatraemia. Tolvaptan is an oral, highly selective arginine vasopressin V2-receptor antagonist, which has been licensed in adults for the management of SIADH and has been used in treating paediatric heart failure. Tolvaptan gradually increased sodium levels and allowed liberalisation of fluid intake and hyperhydration. Tolvaptan had profound effects on urinary output in our patient with increases up to 8 mL/kg/h and required close monitoring of fluid balance, frequent sodium measurements and adjustments to intake. After hyperhydration, tolvaptan was stopped, and the lymphoma went into remission with reversal of SIADH. We report one of the first uses of tolvaptan in a child with SIADH, and it was an effective and safe treatment to manage severe SIADH when fluid restriction was not possible or effective. However, meticulous monitoring of fluid balance and sodium levels and adjustments of fluid intake are required to prevent rapid sodium changes. Learning points: Tolvaptan can be used in paediatric patients with SIADH to allow hyperhydration during chemotherapy. Tolvaptan has profound effects on urinary output and meticulous monitoring of fluid balance and sodium levels is therefore warranted. Tolvaptan was well tolerated without significant side effects.